Peran Konektivitas Dalam Pembangunan Ekonomi Kepulauan Provinsi Maluku Utara - Yetty; Chairullah Amin; Zulkifli Waibot (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
The study emphasizes the importance of connectivity in the economic development of the islands of North Maluku province. The research method uses path analysis techniques to explain the causal relationship between connectivity variables, inflation, economic growth, and poverty. The results show a negative relationship between inflation and economic growth, a positive relationship with economic growth, a negative relationship between economic growth and poverty, and a negative relationship between connectivity and poverty. The results emphasize the importance of developing connectivity in archipelagic areas with a high level of vulnerability in their economic development.